2019
DOI: 10.1002/uog.20100
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal mortality, timing of delivery and prenatal management of monoamniotic twin pregnancy: systematic review and meta‐analysis

Abstract: MCMA twins are at high risk of perinatal loss during the third trimester of pregnancies, with the large majority of such losses occurring as apparently unexpected events. Inpatient management seems to be associated with a low rate of mortality although further studies are needed in order to establish the appropriate type and timing of prenatal assessment in these pregnancies. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 39 publications
(61 reference statements)
0
60
0
6
Order By: Relevance
“…To date, SET policy has become the central strategy in many IVF centers, as it has ability to reduce the rate of multiple pregnancies which are known to be associated with adverse maternal and neonatal outcomes . In this meta‐analysis, we observed that day 6 BET are associated with lower pregnancy outcomes than day 5 BET following SET cycle, while transferring more than two day 5 blastocysts is associated with similar pregnancy outcomes compared with transferring same number of day 6 blastocysts.…”
Section: Discussionmentioning
confidence: 69%
“…To date, SET policy has become the central strategy in many IVF centers, as it has ability to reduce the rate of multiple pregnancies which are known to be associated with adverse maternal and neonatal outcomes . In this meta‐analysis, we observed that day 6 BET are associated with lower pregnancy outcomes than day 5 BET following SET cycle, while transferring more than two day 5 blastocysts is associated with similar pregnancy outcomes compared with transferring same number of day 6 blastocysts.…”
Section: Discussionmentioning
confidence: 69%
“…There are no randomized controlled trials comparing the different management protocols in MCMA twin pregnancies. There is also wide variation in practice with regard to the type and frequency of fetal monitoring and timing of initiation of fetal surveillance among recently published studies. Fortnightly ultrasound assessment and prompt referral of cases affected by TTTS to centers with high expertise in fetal surgery have led to a significant reduction in the rate of perinatal mortality in MCDA twin pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence of fetal loss in MCMA twin pregnancies is approximately 6%, the large majority of which occur before 30 weeks' gestation. TTTS can also occur in MCMA twin pregnancies, although its incidence has been reported to be 2.4 to 2.7 times lower than in MCDA twin gestations. The lower incidence of TTTS in MCMA pregnancies probably reflects the different anastomotic pattern observed in monoamniotic gestations, in which there is a higher prevalence of arterioarterial anastomoses, which are protective against the occurrence of this pathology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations